CEO Power and Corporate Credit Ratings: Evidence from U.S. Companies - Ngo, Thu Trang (2018)
This paper examines the relationship between CEO power and corporate credit ratings, using a sample of non-financial U.S. companies that are rated by the Standard and Poor’s during the period between 2013 and 2016. The study focuses on two dimensions of CEO power: structural and ownership power. Structural power is proxied by three variables: CEO’s Pay Slice – the proportion of aggregate compensation of five highest-paid executives that is rewarded to the CEO, Title concentration – whether the CEO serves as both the President of the firm and the Chairman of the board, and CEO Power score – an index which incorporates different interpretations of CEO dominance, including whether the CEO is the sole signer of the letter to shareholders. Ownership power is measured by two indicators: CEO’s status as a founder of the firm or a close relative of the founders, and the percentage of firms’ outstanding shares owned by the CEOs. Empirical results show that not every dimension of CEO power has an influence on corporate credit ratings. While CEO structural power has a significant impact on firms’ credit ratings, CEO ownership power does not. Moreover, empirical evidence reveals that CEO structural power is positively associated with corporate ratings, suggesting that firms with powerful CEOs are perceived favourably by credit rating agencies and therefore, receive higher ratings.